Optimalkan Kinerja Pegawai: Kedisiplinan dan Kompensasi di Kantor Badan Pendapatan Daerah Kabupaten Sidrap - Hastianti, Hastianti; D’ornay, Anastasia; Angka, Andi FItri Sugi; Syamsuriani, Syamsuriani (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This study aims to find out and find the relationship that exists in the variables of discipline and compensation on employee performance at the Regional Revenue Agency (BAPENDA) of Sidrap Regency, both partially and simultaneously. The analytical method used in this study is Multiple Linear Regression Analysis, Validity Test, Reliability Test, Partial Test (t test), Simultaneous test (F test) and Coefficient of Determination Test (R2 test) with 43 respondents. The results showed that discipline (X1) has a positive and partially significant effect on the performance (Y) of employees at the Regional Revenue Agency (BAPENDA) Sidrap Regency, with a t-count value of 3.463 > t-table 2.021 and a significant value of 0.001 <0, 05. Compensation (X2) has a positive and partially significant effect on the performance (Y) of employees at the Regional Revenue Agency (BAPENDA) Sidrap Regency with a t-count value of 3.391 > t table 2.021 and a significant value of 0.001 <0.05. Each variable has a positive and significant simultaneous effect on the performance of employees at the Regional Revenue Agency of Sidenreng Rappang Regency with an F-count of 52,582 > F-table 3.23 and a significant value of 0.000 <0.05.